REMOVAL OF ORGANIC COMPOUNDS RESULTED FROM BIODEGRADATION PROCESS ON ORIGINAL AND ARTIFICIAL VARIATE OF LIQUID BIOWASTE USING ANAEROBIC BATCH REACTOR SYSTEM - DIAN WAHYU ADIB PUTRI (NIM 15306047); Pembimbing: Dr. Ir. Mindriany Syafila, M.S., SYLVINA
The objection of this final project is the degradation process of biowaste in liquid fraction which derived from fruits and vegetables waste of traditional market, with 2 variations of compositions : the original variate (directly derived from the traditional marketÃ‚Â’s organic waste) and the artificial variate (derived from chosen fruits and vegetables which collected separatedly by the type and mixed with composition 50:50). The degradation process are conditioned using Anaerob Batch Reactor System. Organic waste which used here derived from Pasar Caringin, Bandung. The operation process of batch reactors consist of mechanical process (segregation, grinding, mixing and separation) and biological process (anaerobic process using batch reactor). These steps can obtained organic waste in liquid, slurry, and solid fraction, but this study used only the liquid fraction. The examined parameters are temperature, pH, Total Volatile Acid (TVA), Soluble Chemical Oxygen Demand (COD), ethanol and biogas composition. The reactors are operated twice, each reactor are operated in 10 days. In 10 days of operation, the degradation process expected to have reached fermentation phase (asidogenesa) of degradation, which is indicated by occurance of fermentation products, such as TVA, ethanol, H2, CO2, biogas, and removal of soluble COD. The soluble COD removal efficiency was 81.82% and 79.167% for running 1 and 72.73% and 75% for running 2.